Prawne i ekonomiczne aspekty zatrudniania zawodników spoza = UE The legal and economic aspects of hiring non-EU players - Daria Pałucka; Mateusz Tomanek (Kazimierz Wielki University, 2016)
Pałucka D., Tomanek M. Prawne i ekonomiczne aspekty zatrudniania zawodników spoza UE = The legal and economic aspects of hiring non-EU players. Journal of Education, Health and Sport. 2016;6(8):747-767. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.155096 http://ojs.ukw.edu.pl/index.php/johs/article/view/3871 https://pbn.nauka.gov.pl/sedno-webapp/works/749179     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 08.09.2016. Revised 13.09.2016. Accepted: 21.09.2016. Streszczenie Treść artykułu dotyczy sposobów zatrudniania w polskich klubach sportowych zawodników spoza UE. W pierwszym etapie (badania poznawcze), zaprezentowano aktualny zbiór aktów prawnych prawa polskiego, oraz rozstrzygnięcia Trybunału Sprawiedliwości Unii Europejskiej, które mogą posłużyć za temat dalszych rozważań w zakresie możliwości zatrudniania obcokrajowców - zarówno posiadających obywatelstwo jednego z państw członkowskich UE, jak i osób spoza Unii Europejskiej. Przedstawiono również regulacje wybranych polskich związków sportowych dotyczących tego zagadnienia. Drugą część artykułu stanowią wyniki badań dot. współpracy klubów sportowych z urzędami wojewódzkimi, która jest wymagana podczas składania wniosków o zezwolenie na pracę.     Abstract The article describes how the employment of non-EU players in Polish sporting clubs look like. The first stage (cognitive research) consists of an updated collection of acts of the Legal Polish law and verdicts of the European Court of Justice, which can serve as the subject of further considerations in terms of possibilities on how to employ foreigners - both, having the nationality of one of the member states of the EU and as well as of those who don't. The second part of the article consists of the research results concerning the cooperation between the sports clubs with the provincial department which is necessary while applying forms for work permits.